Relationship Between Helicobacter pylori Infection Fasting Plasma Glucose Concentration Bordering - Meroj A. Jasem; Ali H. Alwan; Fatin M. Mahdi (College of Pharmacy / Mustansiriyah University, 2010)
Helicobacter pylori gastritis results in an increased secretion of basal and meal-stimulated gastrin, which is also a physiologic amplifier of insulin release. Aim of the study: To detect the relationship between H. pylori infection and fasting blood glucose concentration. The study was performed on 209 patients (112 females and 97 males) and 22 control subjects were referring to Immunology Dep. in Central Public Health Laboratories for the period from August 2007 to June 2008, where H.pylori was diagnosed serologically. Fasting serum glucose concentrations had been measured by the glucose oxidase procedure. The fasting plasma glucose was significantly lower in H. pylori infected patients than non-infected ones. Seropositive anti-H.pylori IgG antibodies were detected in 36.6% of women participants (41/112) and in 37.1% of men participants (36/97). The research findings indicate a positive association between H. pylori infection and fasting serum glucose concentrations, indicating that H. pylori infection and related gastrointestinal disorder may be related to glycaemic status.